1999
DOI: 10.1046/j.1469-8137.1999.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of thermal adaptation by high‐latitude cyanobacteria

Abstract: Although mat-forming cyanobacteria dominate many freshwater ecosystems in the Arctic and Antarctic, their optimal temperature for growth (T opt ) is usually much higher than the temperature range of their native habitat. The present study compared the temperature dependence of growth, pigment composition and absorbance, photosynthesis and photosynthate partitioning for two strains of cyanobacteria with contrasting T opt values ; Phormidium subfuscum, isolated from McMurdo Ice Shelf, Antarctica, and Phor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 51 publications
8
30
0
Order By: Relevance
“…Our results show that the reduction of the chlorophyll a content is much more pronounced in C. raciborskii compared to A. gracile, resulting in a steep increase of the carotenoid to chlorophyll a ratio in C. raciborskii, especially of the 4-hydroxymyxol glycoside to chlorophyll a ratio. The high carotenoid to chlorophyll a ratio that we found at suboptimal low and high temperatures has also been observed in polar cyanobacteria (Tang et al, 1997;Tang & Vincent, 1999). Consistent with the present study, polar cyanobacteria were more prone to photoinhibition at low temperatures as well as at temperatures above the optimum.…”
Section: Discussionsupporting
confidence: 81%
“…Our results show that the reduction of the chlorophyll a content is much more pronounced in C. raciborskii compared to A. gracile, resulting in a steep increase of the carotenoid to chlorophyll a ratio in C. raciborskii, especially of the 4-hydroxymyxol glycoside to chlorophyll a ratio. The high carotenoid to chlorophyll a ratio that we found at suboptimal low and high temperatures has also been observed in polar cyanobacteria (Tang et al, 1997;Tang & Vincent, 1999). Consistent with the present study, polar cyanobacteria were more prone to photoinhibition at low temperatures as well as at temperatures above the optimum.…”
Section: Discussionsupporting
confidence: 81%
“…As observed for chl a concentration, net primary productivity values inferred from oxygen microprofiles in artificial microbial mats were lower than data published for non-polar environments but were in the range of those reported for natural Antarctic microbial mats (Table 2). These observations are consistent with recent studies indicating that psychrotrophic cyanobacteria reduced their chl a content and their photosynthetic capacity at low temperatures (Tang et al 1997a, Tang & Vincent 1999. Thus, collective considerations of pigment content and primary productivity indicated that the artificial microbial mats presented some characteristics of natural polar mats, although some differences between artificial mats and field mat have been determined.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, effects of temperature, and especially mechanisms of adaptation to cold by mat-forming cyanobacteria, have been a major research focus (Tang et al 1997a, Roos & Vincent 1998, Tang & Vincent 1999. Experimental studies from polar cyanobacterial isolates have shown that many of these microorganisms can adjust their pigment content and photosynthetic capacity to optimise their growth over a broad temperature range (Tang et al 1997, Tang & Vincent 1999. Recently, psychrophilic mat-forming cyanobacteria isolated from Antarctic meltwater ponds have been characterised; however, little is known about cold-adaptation processes in Antarctic mats (Nadeau & Castenholz 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria, including picocyanobacteria, are known to be of widespread importance in polar freshwater environments, including northern rivers (Rae & Vincent 1998), and are typically observed in low or negligible abundance in polar seas. This latter observation has been attributed to the cold-tolerant but not psychrophilic growth characteristics of high-latitude cyanobacteria (Tang & Vincent 1999) and their inability to keep pace with loss processes such as advection and grazing in cold oceans (Vincent et al 2000). Although picocyanobacteria were a minor constituent of the offshore heterotrophic prokaryote communities, their concentrations were higher than at equivalent latitudes in Antarctica, perhaps reflecting their continuous input into the Arctic Ocean from freshwater sources.…”
Section: Discussionmentioning
confidence: 99%